Dishonesty and Public Employment - Cruces, Guillermo Antonio (2020)
We study the link between dishonesty and selection into public employment. When military conscription was mandatory in Argentina, eligibility was determined by a lottery and by a medical examination. In order to avoid conscription, drafted individuals had strong incentives to cheat in their medical examination. These incentives varied with the lottery number. Exploiting this exogenous variation in the propensity to engage in dishonest behavior during early adulthood (the “impressionable” years), we find that individuals with higher probability of having cheated in their health checks as young adults also show higher propensity to become public employees later in life.